Association between Helicobacter pylori infection and serum thyroid stimulating hormone in the National Health and Nutrition Examination Survey 1999-2000 - Wang, Jinyun; Liu, Dingwei; Xie, Yong (Frontiers in Endocrinology, 2022)
Objective Current evidence on the associations between plasma thyroid stimulating hormone and Helicobacter pylori infection is conflicting. Therefore, our study aimed to examine TSH in relation to H. pylori infection. Methods Based on the US National Health and Nutrition Examination Survey (NHANES) 1999-2000, a cross-sectional study was conducted with 948 participants aged 30 to 85 years. The associations between H. pylori seropositivity and TSH were evaluated using binary logistic regression models. A subgroup analysis stratified by sex, age, and body mass index was conducted. Results A higher serum TSH level was found in subjects with H. pylori seropositive than in subjects with H. pylori seronegative. A significant positive association was found between H. pylori seropositivity and TSH with increasing quartiles of hormonal levels in univariate regression models (Q4 vs Q1: OR = 1.659; 95% CI, 1.152-2.389) and in multivariate regression models (Q4 vs Q1: OR = 1.604; 95% CI, 1.087-2.367). In stratified analyses, the adjusted association of serum TSH with H. pylori seropositivity was statistically significant in male (Q4 vs Q1: OR = 1.894; 95% CI, 1.109-3.235), normal BMI (Q4 vs Q1: OR = 1.894; 95% CI, 1.109-3.235), overweight (Q4 vs Q1: OR = 2.124; 95% CI, 1.047-4.308);, obese (Q4 vs Q1: OR = 0.429; 95% CI, 0.220-0.837), and age over 60 years (Q4 vs Q1: OR = 1.999; 95% CI, 1.118-3.575). Conclusion High TSH levels were associated with H. pylori infection, especially among male, overweight and elderly adults.